The economics of electricity storage - Nyamdash, Batsaikhan (Trinity College (Dublin, Ireland). Department of Economics, 2011)
This thesis investigates the issues surrounding electricity storage systems from various perspectives. It assesses the impact on the power system operation and the resulting benefits for developers versus system operators. It then examines the impact of storage on electricity prices in a gross pool market. The wider economic benefits are then considered through examination of gross value added.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.